2016
DOI: 10.1007/s00484-016-1180-5
|View full text |Cite
|
Sign up to set email alerts
|

Shading effect on microclimate and thermal comfort indexes in integrated crop-livestock-forest systems in the Brazilian Midwest

Abstract: The objective of this paper was to perform a microclimate evaluation and determine the indexes of thermal comfort indexes, in sun and shade, in integrated crop-livestock-forest systems with different arrangements of eucalyptus and native trees, in the Brazilian Midwest. The experiment was conducted at Embrapa Beef Cattle in Campo Grande, state of Mato Grosso do Sul, Brazil, from July to September 2013. The evaluations were conducted on four consecutive days, from 8:00 a.m. to 5:00 p.m., local time (GMT -4:00),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 20 publications
(33 reference statements)
3
44
0
2
Order By: Relevance
“…In January of 2017, Brazil launched its National Plan for the Recovery of Native Vegetation [3] to promote forest restoration programs and actions. Besides that, another incentive by the Brazilian government is the Low Carbon Agriculture (LCA) program, which promotes research and extension projects, as well as offering credit lines to finance costs related to the implementation/maintenance of integrated crop-livestock and forest system (iCLF) [4][5][6][7]. These systems deserve to be highlighted as an attractive strategy for restoration [8].…”
Section: Introductionmentioning
confidence: 99%
“…In January of 2017, Brazil launched its National Plan for the Recovery of Native Vegetation [3] to promote forest restoration programs and actions. Besides that, another incentive by the Brazilian government is the Low Carbon Agriculture (LCA) program, which promotes research and extension projects, as well as offering credit lines to finance costs related to the implementation/maintenance of integrated crop-livestock and forest system (iCLF) [4][5][6][7]. These systems deserve to be highlighted as an attractive strategy for restoration [8].…”
Section: Introductionmentioning
confidence: 99%
“…Girolando animals remaining in shades of Mangifera indica in the spring during 64.7% of the 24 hours daily (932.8 min) (Table 3). Karvette et al (2016) reported that the tree canopy can reduce by up to 28.3% the thermal radiation load. According to Biavatti, Berber and Berber (2014), shade in grazing paddocks decreases the animals' thermal stress by providing a better thermal comfort, and increase the animal production.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, when the external temperature is high, this mechanism becomes ineffective and the animals are subjected to a thermal stress, with profound physiological and behavioral changes and significant reduction in food consumption and zootechnical performance. Shadowed areas are required for animals, even in regions with average temperatures below ºC, to mitigate the negative effects of ultraviolet rays; these shadows can be natural or artificial (RODRIGUES;SOUZA;PEREIRA FILHO, 2010;KARVETTE et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this stress has acute effects on cattle welfare, therefore on its productivity either [52]. Thus, a way for lessening such effects is shade usage through the integration of trees to pastures in silvopastoral systems [53] [54], contributing to good welfare for animals [54] [55].…”
Section: Discussionmentioning
confidence: 99%